Hotel website quality influence on customer purchase intention / Muhammad Syazani Ghazali ... [et al.] - Ghazali, Muhammad Syazani; Mohd Shahril, Aslinda; Norzeri, Nur Aina Shuhada; Rosle, Nur Ain Shafika (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
In the hotel industry, a website is an initial place where customers look for information. The website is running at all times and, the website must present information attractively and manage appropriately. Websites are the backbone of digital marketing and selling strategy for hotels and can influence buying behaviour. This study identifies the relationship between website information quality and website system quality in influencing customer purchase intention. This study employed a quantitative method, and a total of 427 respondents participated in this study. A set of self-administered survey questionnaires were distributed using Google Form through Facebook page and WhatsApp to working residents in Selangor. It took about a month to complete the data collection process. The questionnaire was then analyzed using SPSS statistical tool, and it was found that there is a moderate relationship between those variables. The study highlights the importance of system information quality in the hotel website to influence customer purchase intention to book the hotel.